#EndSARS movement in Nigeria: tensions and solidarities amongst protesters. Issue 2 (2nd September 2021) - Nwabunnia, Onyeka Antoinette
ABSTRACT: During Nigeria's #EndSARS movement, queer organisers and activists created and built solidarities that resulted in a truly complex organising for justice. Without the work of queer organisers, the movement to #EndSARS would have largely centred on the narratives and voices of cis heterosexual men and women. In creating systems that sustained the participation of queer protesters both on- and offline, queer organisers ensured that the movement reflected all Nigerians. Situating this article within theoretical debates around political homophobia and transnational feminist solidarities, I will outline the forms of solidarities queer activists developed with each other and the types of tensions that emerged during the movement.